Exploring evolutions in reciprocal peer tutoring groups' socially shared metacognitive regulation and identifying its metacognitive correlates. (August 2015) - De Backer, Liesje; Van Keer, Hilde; Valcke, Martin
Abstract: The present study contributes to the emerging research on socially shared metacognitive regulation (SSMR). It investigates which regulation behaviour (i.e. particular skills and low- versus deep-level regulation) is associated with a socially shared regulation focus and identifies time-bound evolutions in individually-oriented metacognitive regulation, co-regulation, and SSMR. More specifically, higher education reciprocal peer tutoring (RPT) groups are studied. All sessions of a semester-long RPT-intervention of five randomly selected RPT-groups were videotaped (70 h of recordings). Time-bound evolutions are studied by means of mixed models for logistic regression analysis allowing change points, whereas binary logistic regressions are used to examine the relation between RPT-groups' socially shared regulation focus and their regulation skills and approaches. The results indicate that RPT-groups demonstrate a significant positive evolution in SSMR and tutee-prompted co-regulation, and a significant negative evolution in tutor-prompted co-regulation. Their socially shared regulation focus is particularly correlated with orientation, monitoring, and deep-level regulation. Highlights: The adoption of SSMR increases over time. Collaborative learners need time to develop SSMR. SSMR is significantly associated with orienting and monitoring. SSMR is not significantly correlated to planning and evaluating. SSMR shows a stronger association with deep-level compared to low-level regulation.